Maternal self-efficacy and life satisfaction among mothers of children on the autistic spectrum disorder (ASD) and mothers of children with typical development - Greenbank, Alicia; Menzin, Daniela (Journal of Maternal and Child Health, 2024)
Background: The purpose of the present study is to examine the relationship between maternal self-efficacy and life satisfaction among mothers of children on the autistic spectrum disorder (ASD) and mothers of children with typical development. The research hypotheses were about the relationship between the maternal self-efficacy and the satisfaction with life, and about the differences in the maternal self-efficacy and the satisfaction with life between the two groups of mothers. Subjects and Method: The sample consisted of 125 mothers, of which 61 were mothers of children with ASD and 64 were mothers of children with typical development. The mothers answered two online questionnaires: a life satisfaction questionnaire and a maternal self-efficacy questionnaire. Results: The research findings indicated a positive relationship between the maternal self-efficacy and the life satisfaction, so that mothers who reported a higher level of maternal self-efficacy showed higher satisfaction with their lives. Also, differences were found in the life satisfaction between the two groups of mothers: mothers of children with typical development reported a higher satisfaction with life. Contrary to expectations, no differences were found in the maternal self-efficacy between the two groups of mothers. Conclusion: The uniqueness of the study is in the examination of the experience of mothering children with ASD among mothers in Israel, in light of the scant research literature on this subject. In addition, the current study examines the relationship between two important areas: the maternal self-efficacy and the life satisfaction, a relationship about which there is little research both in the context of mothers in general and in the context of mothers of children with ASD in particular. The research findings also have an applied contribution - the findings may help multi-professional teams develop awareness of the experience of mothering a child with ASD, the need for support and accompaniment for mothers and collaborative work with them.